Handbook of innovation in public services (Cheltenham Edward Elgar, 2013)
Innovation is a core issue for public services and is a key element of public services reform - particularly in this age of austerity where policymakers urge the need to 'innovate to do more with less'. This comprehensive and accessible Handbook explores the potential for creating efficient and effective public services.
Includes bibliographical referenCes and index.
Keywords: Public administration